ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI PADI WANITA DI KECAMATAN SAMUDERA KABUPATEN ACEH UTARA - Umaruddin Usman; Mauliza Yanti (Jurnal Ekonomi Pertanian Unimal, 2020)
This study aims to analyze the factors affecting the income of female rice farmers in Samudera District, North Aceh Regency. The data used in this study are primary data, namely women farmers in Samudera District, amounting to 51 people. This research model uses multiple linear regression. The results of the research. Partially, capital, land area and experience affect the income of female farmers in Samudera District. Production costs have a negative effect on the income of female farmers in Samudera District. The amount of production does not affect the income of female farmers in Samudera District